1998
DOI: 10.1002/(sici)1097-4547(19981215)54:6<840::aid-jnr12>3.3.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of insulin‐like growth factor decreases motor neuron cell death and promotes muscle reinnervation

Abstract: Neonatal sciatic nerve axotomy causes motoneuron death and muscle denervation atrophy. The aim of the present study was to determine whether insulin-like growth factor-I (IGF-I) administration promotes muscle reinnervation and counteracts motor neuron loss after such an injury. Six weeks after sciatic nerve axotomy performed in 2-day-old pups, the number of motor neurons, as assessed by retrograde transport of horseradish peroxidase injected into the extensor digitorum longus (EDL) muscle, was reduced from 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…After muscle injury, an inflammatory response is activated, but prolonged accumulation of fibrotic tissue limits muscle cell replacement, leading to less strength and functional depletion compared with normal muscles. The increased force observed in muscles with GFs delivery may also be related to enhanced reinnervation, although the specific mechanisms by which these GFs influence reinnervation remain to be defined (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…After muscle injury, an inflammatory response is activated, but prolonged accumulation of fibrotic tissue limits muscle cell replacement, leading to less strength and functional depletion compared with normal muscles. The increased force observed in muscles with GFs delivery may also be related to enhanced reinnervation, although the specific mechanisms by which these GFs influence reinnervation remain to be defined (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this hypothesis, in mouse models, the overexpression of muscle-specific IGF-1 reverses sarcopenia (Musaro et al, 2001), prevents the age-dependent decrease in type IIB and increase in type IIA fibers (Messi and Delbono, 2003), and also leads to improved nerve regeneration by acting on axons, Schwann cells, and the NMJ. Systemic administration of IGF-1 decreased motor neuron cell death and promoted muscle re-innervation after injury in young animals, suggesting that the decline in IGF-1 with aging may impair the ability of aging animals to repair and maintain the integrity of NMJ (Vergani et al, 1998). IGF-1 sensitivity may not decrease with age, so that IGF-1 could promote regeneration after nerve injury even in older individuals.…”
Section: Biomarkers Of Nmj In Aging and Signaling Pathwaysmentioning
confidence: 99%
“…For example, in young rodents IGF-1 expression is up-regulated in Schwann cells and astrocytes following spinal cord and peripheral nerve injury, while IGF-binding protein 6 is strongly upregulated in injured motorneurones (Hammarberg et al, 1998 Interestingly, in regions of muscle enriched with neuromuscular junctions, IGF-II exhibited prominent up-regulation in satellite and possibly glial cells during recovery from sciatic nerve crush (Pu et al, 1999) while IGF-I showed less significant changes. In young animals, systemic administration of IGF-1 decreases lesion-induced motor neurone cell death and promotes muscle re-innervation (Vergani et al, 1998). IGF-1 also promotes neurogenesis and synaptogenesis in diverse areas of the central nervous system such as the hypocampal dentate gyrus during postnatal development (O'Kusky et al, 2000) or increases proliferation of granule cell progenitors (Ye et al, 1996).…”
Section: Effects Of Igf-1 On Neuronesmentioning
confidence: 99%